Synthesis and characterization of novel spiro-(2,2?-dioxybiphenyl)-cyclotriphosphazene derivatives bearing butylated oxyanisole groups and their antioxidant and antimicrobial activities - Sonmez, Efe Bilal; Un, Sule Sahin; Mutlu Balci, Ceylan; Atilla, Devrim; Seker, Mine Gul; Ibisoglu, Hanife (Pergamon-Elsevier Science Ltd, 2025)
In this study, novel cyclotriphosphazene derivatives, {[N3P3(biph)(BA)(2)] (6a/b), [N3P3(biph)(BA)(3)] (7), [N3P3(biph)(2)(BA)Cl (8) and [N3P3(biph)(2)(BA)(2) (9)]}, (biph = 2 ',2 ''-dioxy-1 ',1 ''- biphenyl, BA = butylated oxyanisole}, were synthesized from the nucleophilic substitution reactions of butylated hydroxyanisole (BHA) (5) with [N3P3(biph)Cl-4] (3) and [N3P3(biph)(2)Cl-2] (4), respectively. The structures of all the products (6a/b, 7, 8 and 9) were determined -using elemental analysis, mass and (H-1 and P-31) NMR spectroscopic techniques. The molecular and crystal structure of compound 9 was also determined by single crystal X-ray crystallography. At the same time, the compounds (3, 4, 7, 8 and 9) were tested for their antimicrobial and antioxidant (free radical scavenging) activities. Of all, compounds 8 and 9 showed relatively significant antimicrobial activity against the control strains Bacillus cereus DSMZ 4312 (16,5 and 18,25 mm) and against Staphylococcus aureus ATCC 29213 (25 and 22,5 mm) compared to their positive controls. The MIC50 values of compounds 8 and 9 against Bacillus cereus were determined at 125 mu g/mL and < 325 mu g/mL, respectively, and Staphylococcus aureus at 125 mu g/ mL for both compounds. While the other compounds (3, 4 and 7) did not possess antimicrobial properties, they showed strong antioxidant activity. In the antioxidant assay based on the EC50 value of BHA used as a control, compound 7 showed antioxidant activity even at low concentrations such as 9,37 mu g/ mL (83 %), while compounds 3 and 4 showed antioxidant properties even at relatively low concentrations such as 18,75 mu g/mL. Compounds 8 and 9, two antimicrobial compounds, did not exhibit antioxidant properties.
Keywords: Cyclotriphosphazene; 2,2 ' -dihydroxybiphenyl; Butylated hydroxyanisole; Antioxidant activity; Antimicrobial activity